Determinants of Economic Growth in OIC Countries: Comparative Analysis by Income Level - Romadhani, Karunia; Nurrizka Puji, Lestari; Herianingrum, Sri; Abdurrahman Mi'raj, Denizar (Universitas Muhammadiyah Yogyakarta, 2025)
Economic growth disparities among OIC member states remain a persistent challenge that demands nuanced, data-driven policy responses. This study investigates the determinants of economic growth in OIC member states from 2010 to 2022. This study offers new insights by analysing four macroeconomic variables, explicitly distinguishing between high and low-income nations. The study's approach provides an in-depth understanding of how each variable impacts different stages of development, supporting more adaptive monetary and fiscal strategies. Panel regression analysis was employed, with a random effects model applied to the low-income country group and a common effects model used for the high-income group. The findings reveal a consistent negative impact of private debt on economic growth across both income groups. In contrast, inflation exhibited no significant influence on economic development in either category. FDI has shown a positive effect on the economic development of high-income countries, while no significant effect was observed for low-income countries. Conversely, trade openness has significantly stimulated economic growth in low-income nations, whereas no significant impact has been observed in high-income countries. Based on these findings, policy recommendations for OIC member states should prioritize debt reduction strategies across all income levels. Policies to enhance FDI in developed economies and promote trade openness are essential for economic growth in low-income OIC member countries.